سعید گوؔہر کی شاعری میں یاسیت۔۔۔۔ ایک مطالعہ (Al-Aasar, 2025)
Saeed Gohar was a famous literary figure from Quatta widely known for his poetic brilliance. Although he was also an accomplished prose writer analyst, it was his poetry that earned him name and fame. His poetic expression is rich with figures of speech like metaphor, symbolism, and stylistic mastery, converting a wide range of themes. However, a significant bulk of his poetry reflects a deep sense of melancholy. This article introduces the concept of melancholy (pessimism) and explore its presence in Saeed Gohar’s poetry. His verses give vent to the feelings of sorrow, pain, loneliness, personal suffering, and the cruelty of time all of which contribute to a profound sense of sadness that runs through the threads of his word.